2008
DOI: 10.1203/pdr.0b013e31816c8fcc
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Serum Cortisol Concentrations in Preterm Infants With or Without Late-Onset Circulatory Collapse due to Adrenal Insufficiency of Prematurity

Abstract: A recent survey found that approximately 4% of very low birth weight infants in Japan were treated with glucocorticoids postnatally for circulatory collapse thought to be caused by late-onset adrenal insufficiency. We identified 11 preterm infants with clinical signs compatible with this diagnosis (hypotension, oliguria, hyponatremia, lung edema, and increased demand for oxygen treatment) and matched them for gestational age with 11 infants without such signs. Blood samples were obtained for cortisol and its p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
107
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(110 citation statements)
references
References 34 publications
1
107
0
2
Order By: Relevance
“…Identifying infants with relative adrenal insufficiency is difficult; measuring cortisol levels may be useful, however, studies have shown that low cortisol levels are not helpful in defining a population who would benefit from HC therapy. 10,15,16 In our case, information regarding cortisol levels before treatment was not available. Interestingly, those infants who were not pretreated with prophylactic stress HC but subsequently required HC for pressor-resistant hypotension were not clinically different from others in the non-treated group, indicating the challenge of identifying these infants prospectively.…”
Section: Discussionmentioning
confidence: 87%
“…Identifying infants with relative adrenal insufficiency is difficult; measuring cortisol levels may be useful, however, studies have shown that low cortisol levels are not helpful in defining a population who would benefit from HC therapy. 10,15,16 In our case, information regarding cortisol levels before treatment was not available. Interestingly, those infants who were not pretreated with prophylactic stress HC but subsequently required HC for pressor-resistant hypotension were not clinically different from others in the non-treated group, indicating the challenge of identifying these infants prospectively.…”
Section: Discussionmentioning
confidence: 87%
“…The pathophysiological mechanism underlying LCC is thought to be relative adrenal insufficiency, because the circulatory failure responds to glucocorticoid therapy but not to volume loading or vasopressors (Masumoto et al 2008). LCC may result from the suppression of fetal cortisol production until late in the gestational period by interaction between the fetal hypothalamic-pituitary-adrenal axis and the placenta (Mesiano and Jaffe 1997;Kapoor et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiological mechanism underlying LCC is thought to be relative adrenal insufficiency (Masumoto et al 2008). Levothyroxine replacement has been implicated as one of the factors that provoke LCC (Takizawa et al 2010;Yagasaki et al 2010;Kawai et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Before cutting umbilical cord, promoting placental-fetal transfusion by cautious cord milking is helpful to maintain adequate blood volume of the infant [12]. Often postnatal steroid administration is essential to stabilize blood pressure to encounter adrenal cortical insufficiency due to extreme prematurity and stress [13]. Use of umbilical venous catheter as an infusion route for the first 5 to 7 days is inevitable to avoid excess handling to keep peripheral lines [9].…”
Section: Discussionmentioning
confidence: 99%